Inhibition of Caco-2 and MCF-7 cancer cells using chalcones: synthesis, biological evaluation and computational study. Issue 17 (1st September 2022) - Mellado, Marco; Reyna-Jeldes, Mauricio; Weinstein-Oppenheimer, Caroline; Coddou, Claudio; Jara-Gutierrez, Carlos; Villena, Joan; Aguilar, Luis F.
Abstract: Cancer is the second death cause worldwide, with breast and colon cancer among the most prevalent types. Traditional treatment strategies have several side effects that inspire the development of novel anticancer agents derived from natural sources, like chalcone derivatives. For this investigation, twenty-three chalcones (4a-w ) were synthesized and evaluated as antiproliferative agents against MCF-7 and Caco-2 cells, finding three and two compounds with similar or higher antiproliferative activity than daunorubicin, while only two chalcones showed better selectivity indexes than daunorubicin on MCF-7. From these results, we developed good-performance QSAR models (r > 0.850, q 2 >0.650), finding several structural features that could modify chalcone activity and selectivity. According to these models, chalcones 4w and 4t have high potency and selectivity against Caco-2 and MCF-7, respectively, which make them attractive candidates for hit-to-lead development of ROS-independent pro apoptotic agents. Graphical Abstract: UF0001